2020
DOI: 10.1002/jcc.26452
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of lattice energy of benzene crystals: A robust theoretical approach

Abstract: We present an inexpensive and robust theoretical approach based on the fragment molecular orbital methodology and the spin-ratio scaled second-order Møller-Plesset perturbation theory to predict the lattice energy of benzene crystals within 2 kJÁmol −1. Inspired by the Harrison method to estimate the Madelung constant, the proposed approach calculates the lattice energy as a sum of two-and three-body interaction energies between a reference molecule and the surrounding molecules arranged in a sphere. The latti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 101 publications
(164 reference statements)
1
14
0
Order By: Relevance
“…Benzene clusters for both form I and form II demonstrate a smooth behavior in non‐CP corrected HF energies with increasing cluster size. It has been recently shown that three‐body effects are rather negligible in crystal structures of both forms 3 . Therefore, such smooth behavior is expected.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Benzene clusters for both form I and form II demonstrate a smooth behavior in non‐CP corrected HF energies with increasing cluster size. It has been recently shown that three‐body effects are rather negligible in crystal structures of both forms 3 . Therefore, such smooth behavior is expected.…”
Section: Resultsmentioning
confidence: 93%
“…It has been recently shown that three‐body effects are rather negligible in crystal structures of both forms. 3 Therefore, such smooth behavior is expected. With introduction of non‐additive interactions such as induction forces present in hydrogen‐bonded clusters of ODH and to some extent in aspirin, the non‐CP corrected HF energies behave differently, no longer exhibiting a smooth behavior with increasing cluster size.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…The method can be applied to crystals containing other systems such as DNA with the practical limitation that for some chemical elements DFTB parameters may not be available. Using optimized structures, one can estimate properties such as the lattice energy and gain insight into interactions in crystals with the developed partition analysis. This analysis can be used without fragmentation with possible future applications not only to crystals of macromolecules but to molecular crystals in general and to other systems treated with the PBC such as proteins in solution.…”
mentioning
confidence: 99%